2005
DOI: 10.1016/j.jmhg.2004.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Male androgenetic alopecia (Part II)

Abstract: Androgenetic alopecia only becomes a medical problem when the hair loss is excessive, premature and distressing to the patient. A number of medical treatments aimed at arresting the progression of the hair loss have become available in recent years, and surgical treatments are constantly being refined. The three distinct aims of therapy for male androgenetic alopecia are: to arrest further progression, to stimulate regrowth and to conceal the hair loss. Topical minoxidil stimulates regrowth but may or may not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…The regional specificity of androgen action is also partly explained by in vitro experiments, where androgen stimulation of scalp DPCs induced TGF-β1 production, while stimulation of beard DPCs induced IGF-1 as a second messenger [24]. Itami et al observed that the synthetic androgen R1881 suppressed keratinocyte growth in the coculture of AR-overexpressing human DPCs from AGA and normal human keratinocytes, through androgeninducible TGF-β1 [22,25].…”
Section: Androgens and Hair Folliclesmentioning
confidence: 99%
“…The regional specificity of androgen action is also partly explained by in vitro experiments, where androgen stimulation of scalp DPCs induced TGF-β1 production, while stimulation of beard DPCs induced IGF-1 as a second messenger [24]. Itami et al observed that the synthetic androgen R1881 suppressed keratinocyte growth in the coculture of AR-overexpressing human DPCs from AGA and normal human keratinocytes, through androgeninducible TGF-β1 [22,25].…”
Section: Androgens and Hair Folliclesmentioning
confidence: 99%
“…The weight of hair is influenced by factors such as hair density, hair growth rate, and hair thickness. These studies demonstrate finasteride's capacity to counteract the shrinking process, resulting in longer and thicker hair, maybe with an increased growth rate [52] . 2.…”
Section: Topical Antifungal and Antibioticsmentioning
confidence: 70%
“…In addition, the spread of BU is enhanced by a lower death rate of humans. Equation (11) shows that the prevalence of BU in humans depends on the biting rate of water-bugs, their mortality rate and As concentration in the environment. For BU, a is relatively smaller than m, thus the prevalence of BU (see equation (11)) in humans and MU in waterbugs (equation (15)) increases for R 0 .…”
Section: Model Variables and Parametersmentioning
confidence: 99%
“…Recreational activities near rivers where MU persists could lead to costly BU infection. Considering the fact that the cost of swimming related illnesses in only two beaches of Orange County in California, for example, is estimated to be over USD 3 million per year [11], an outbreak of BU could lead to substantially higher health costs since water recreation is enjoyed by a greater proportion of the population in developed countries.…”
Section: Introductionmentioning
confidence: 99%